Representation of Women in the Layangan Putus Film Series: Semiotic Analysis of Roland Barthes - Hanifah, Ummy; Ningsih, Titiek Surya (Fakultas Dakwah UIN Saizu Purwokerto, 2023)
The film has the power to influence gender ideology. The preservation of gender ideology can be noticed in the portrayal of women as weak people who are always intimidated both physically, sexually, and economically. The image of women as weak creatures is depicted in the Layangan Putus film series. These film series reach the highest rank in several Southeast Asian countries. The film describes a wife's pressure from her husband's affair and her struggle to overcome it. This study aims to analyze the representations of women in the context of images and scenarios in a film shown in the film series Layangan Putus using Roland Barthes' semiotic approach. Barthes introduces the concept of denotation, connotations, and myths. The results revealed that the denotation analysis and connotation level in the Layangan Putus film series confirm women's opposition to gender roles. Furthermore, this opposition aligns with Liberal Feminism seeking to liberate women from male domination. Liberal feminists aim to liberate women from gender-based constraints, challenging the lower status assigned to them solely due to their sex. On the other hand, true equality can be achieved by embracing androgynous perspectives, recognizing that both men and women possess characteristics of femininity and masculinity.